2010
DOI: 10.1093/brain/awq261
|View full text |Cite
|
Sign up to set email alerts
|

A novel cerebello-ocular syndrome with abnormal glycosylation due to abnormalities in dolichol metabolism

Abstract: Cerebellar hypoplasia and slowly progressive ophthalmological symptoms are common features in patients with congenital disorders of glycosylation type I. In a group of patients with congenital disorders of glycosylation type I with unknown aetiology, we have previously described a distinct phenotype with severe, early visual impairment and variable eye malformations, including optic nerve hypoplasia, retinal coloboma, congenital cataract and glaucoma. Some of the symptoms overlapped with the phenotype in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 40 publications
10
110
1
Order By: Relevance
“…Previously, CVI has been reported as part of congenital disorders of glycosylation (CDG) type 1a (PMM2), type 1q (SRD5A3), and type 1v (NGLY1). 8,28,30,31 The phenotype of patient 2 with NGLY1 variants is similar to the previously reported patients, including the microcephaly, hypotonia, movement disorder, and alacrima. 28,32,33 Variants in SLC35A2 lead to CDG type 2m, featured by ID, epilepsy, facial dysmorphisms, and transient abnormalities in transferin testing.…”
Section: Resultssupporting
confidence: 84%
“…Previously, CVI has been reported as part of congenital disorders of glycosylation (CDG) type 1a (PMM2), type 1q (SRD5A3), and type 1v (NGLY1). 8,28,30,31 The phenotype of patient 2 with NGLY1 variants is similar to the previously reported patients, including the microcephaly, hypotonia, movement disorder, and alacrima. 28,32,33 Variants in SLC35A2 lead to CDG type 2m, featured by ID, epilepsy, facial dysmorphisms, and transient abnormalities in transferin testing.…”
Section: Resultssupporting
confidence: 84%
“…Their conclusions were based foremost on mutations in SRD5A3 in a large Emirati family from Baluchi (Southern Iran) and children from seven other families. Subsequently, other studies also identified mutations in patients further supporting SRD5A3 as associated with CDGs (Gründahl et al, 2012;Kahrizi et al, 2011;Kasapkara et al, 2012;Morava et al, 2010). Interestingly, these patients exhibited residual dolichol levels, implying that there must be an alternative pathway for dolichol biosynthesis Gründahl et al, 2012).…”
Section: Biosynthesis Of the Eukaryotic Dolichyl Lipid Carriersmentioning
confidence: 90%
“…Although the presence of multiple enzymes was initially suggested , Godoy et al 2011, genes encoding two isozymes (SRD5A1 and SRD5A2) were later cloned in the 1990s (Andersson & Russell 1990, Andersson et al 1991. SRD5A1 and SRD5A2 are members of a larger family of genes containing 5a-reductase domains, the other members being encoded by the genes SRD5A3 and GPSN2-SRD5A2L2, whose roles remain less clear, but may involve reduction of non-steroidal substrates (Cantagrel et al 2010). SRD5A3 was identified through expression profiling of hormone refractory prostate cancer cells and its transcript is expressed in higher levels in malignancy in comparison with benign tissues (Uemura et al 2008, Yamana et al 2010, Godoy et al 2011.…”
Section: Therapeutic Actions Of Gcs To Relieve Inflammationmentioning
confidence: 99%
“…To date, similar catalytic activities have not been demonstrated for GCs. However, a distinct role for this enzyme has been proposed to catalyse conversion of polyprenol to dolichol and mutations in SRD5A3 give rise to a congenital disorder of glycosylation (Cantagrel et al 2010, Morava et al 2010, Kahrizi et al 2011.…”
Section: Therapeutic Actions Of Gcs To Relieve Inflammationmentioning
confidence: 99%